Tile Drainage Increases Total Runoff and Phosphorus Export During Wet Years in the Western Lake Erie Basin - Miller, Samuel A.; Lyon, Steve W. (Frontiers in Water, 2021)
Artificial subsurface (tile) drainage is used in many agricultural areas where soils have naturally poor drainage to increase crop yield and field trafficability. Studies at the field scale indicate that tile drains disproportionately export large soluble reactive phosphorus (SRP) and nitrate loads to downstream waterbodies relative to other surface and subsurface runoff pathways, but knowledge gaps remain understanding the impact of tile drainage to nutrient export at watershed scales. The Western Lake Erie Basin is susceptible to summertime eutrophic conditions driven by nonpoint source nutrient pollution due to a shallow mean water depth and land use dominated by agriculture. The purpose of this study is to analyze the impact of tile drainage on downstream discharge, nutrient concentrations, and nutrient loads for 16 watersheds that drain to the Western Lake Erie Basin. Daily discharge and nutrient concentrations were summarized annually and during the main nutrient loading period (March – July) for two years representing relatively normal precipitation (2018) and above normal precipitation (2019). Results indicate positive correlations between watershed tile drainage percentage and runoff metrics during the above normal precipitation year, but no relationship during the normal precipitation year. Additionally, SRP concentration and load were positively correlated to watershed tile drainage percentage in the above normal precipitation year, but not in the year with normal precipitation. Watershed tile drainage percentage was correlated with nitrate concentration and load for both years. The SRP concentration-discharge relationships suggested relatively weak, chemodynamic behavior, implying a slight enriching effect where SRP concentrations were greater at higher stream discharge conditions during both years. In contrast, nitrate concentration-discharge relationships suggested strong, enriching chemodynamic behavior during the average precipitation year, but chemostatic behavior during the above normal precipitation year. The difference in SRP and nitrate export patterns in the two years analyzed highlights the importance of implementing appropriate best management practices that target specific nutrients and treat primary delivery pathways to effectively improve downstream aquatic health conditions.